Parkification of Post-Industrial Sites: A Catalyst for Greenway Development in Ruseifa, Jordan - Kawthar Alrayyan (Fábos Conference on Landscape and Greenway Planning, 2025)
<p class="MsoNormal" style="margin: 0in 0in 12pt; line-height: normal; font-size: 11pt; font-family: Calibri, sans-serif; color: rgb(0, 0, 0); font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none; text-align: justify;">Three parkification projects in Ruseifa city, Jordan were initiated simultaneously in 2020. These novel projects have transformed three post-industrial sites into urban parks to address their environmental, ecological and social challenges posed by these abandoned sites. Rather than focusing solely on the parks themselves, this study examines the parkification process and its unique characteristics across these sites. It explores the events, processes, and key actors involved in their transformation. By unravelling these processes, the study highlights their potential as incubators for greenway development and environmental sustainability in the region. <p class="MsoNormal" style="margin: 0in 0in 8pt; line-height: 15.693334px; font-size: 11pt; font-family: Calibri, sans-serif; color: rgb(0, 0, 0); font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Utilizing semi-structured interviews with decision-makers and stakeholders involved in these projects, coupled with content analysis of relevant documents, reports, and policies, the study distinguished three different parkification processes for the selected sites: 1) Restoration and environmental remediation at the Pepsi Pond site, 2) Environmental rehabilitation at the phosphate ore landfill site and 3) Industrial heritage preservation at the old phosphate mine and administration building site. <p class="MsoNormal" style="margin: 0in 0in 8pt; line-height: 15.693334px; font-size: 11pt; font-family: Calibri, sans-serif; color: rgb(0, 0, 0); font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none;">Through comparative analysis of these parkification processes, and an examining of the decision-making factors influencing the decision of parkification, this study forms a foundational step towards integrated greenway systems, benefiting from the close proximity of the three sites, as illustrated in Figure 1. <p class="MsoNormal" style="margin: 0in 0in 12pt; line-height: normal; font-size: 11pt; font-family: Calibri, sans-serif; color: rgb(0, 0, 0); font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none; text-align: justify;">By analysing these parkification processes, this study aims to address a significant research gap, providing valuable insights and benchmarks for future initiatives in Ruseifa and beyond. This investigation not only contributes to the broader discourse on landscape transformation but also serves as a strategic approach to promote greenway development, foster community engagement, and enhance environmental sustainability in Ruseifa and similar contexts. <p class="MsoNormal" style="margin: 0in 0in 12pt; line-height: normal; font-size: 11pt; font-family: Calibri, sans-serif; color: rgb(0, 0, 0); font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none; text-align: justify;"> <p class="MsoCaption" style='margin: 0in 0in 12pt; font-size: 9pt; font-family: "Times New Roman", serif; color: rgb(68, 84, 106); font-style: italic; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration: none; text-align: center; line-height: 13.8px;'> Figure.1: Site map for the three selected post-industrial sites in Ruseifa City, Jordan. Site 1: Pepsi Pond; Site 2: Phosphate Ore Hills; Site 3: Phosphate Old Mines & Administration Building. Source: Author, 2023.
Keywords: Parkification; Post-industrial; Greenway; Ruseifa